Research Paper: Fabrication of DSSCs Based on Ag-Decorated TiO2 Nanofiber Photoanodes - Ahmad Zatirostami; Khikmat Muminov; Alimakhmad Kholov; Farshid Mofidnakhaei (فیزیک کاربردی ایران, 2022)
Dye-sensitized solar cells (DSSCs) are cheap and earth abundant solar cells that require novel ideas for further improvement. In this study, we use TiO2 nanofibers to fabricate the DSSCs photoanode. In order to isolate the transparent conductive oxide from the electrolyte species, we deposit a spin-coated TiO2 blocking layer. The characteristics of this cell are further improved by decorating the nanofibers with Ag nanoparticles which generate surface plasmonic resonances. It is shown that LSPRs increase the generated current in the cells by providing a higher light absorption and lower recombination. Our best cell showed an efficiency of 6.19%, which is a significant improvement in comparison to the bare DSSC with 4.84% efficiency.